Analisa Kesulitan Belajar Bahasa Indonesia Siswa Kelas 4A di SDN Margamulya VI Bekasi - Salman Ulwan Zulfan; Ibnu Muthi (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze learning difficulties in Bahasa Indonesia among 4th grade students at SDN Margamulya VI Bekasi. The researcher employed a qualitative research method for this study. The instruments used were questionnaires and interviews. The research was conducted at SDN Margamulya VI among 4th grade students in the academic year 2024/2025.The findings of this study indicate that the learning difficulty in Bahasa Indonesia experienced by the 4th grade students at SDN Margamulya VI is related to the understanding of paragraph types according to their positions. Factors influencing these difficulties include the students' inability to grasp the abstract concepts of the material.